2001
DOI: 10.1080/02724990042000164
|View full text |Cite
|
Sign up to set email alerts
|

Tests for inhibition after extinction of a conditioned stimulus in the flavour aversion procedure

Abstract: In four experiments, rats received flavour aversion conditioning followed by extinction. The flavour was then subjected to retardation and summation tests. Experiment 1 showed that reacquisition of an extinguished flavour aversion was retarded with respect to the performance shown by rats for whom the flavour was novel. No retardation was found, however, with respect to a control group that had been given non-reinforced pre-exposure to the flavour. Experiment 2 demonstrated that extinction showed the same sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 23 publications
5
41
4
Order By: Relevance
“…A similar asymmetry between reacquisition and latent inhibition has been observed by Aguado et al (2001) in taste-aversion learning. They found that reacquisition after extinction was less retarded than latent inhibition after extensive preexposure to the CS.…”
Section: Stimulus Processing Modelsmentioning
confidence: 50%
See 2 more Smart Citations
“…A similar asymmetry between reacquisition and latent inhibition has been observed by Aguado et al (2001) in taste-aversion learning. They found that reacquisition after extinction was less retarded than latent inhibition after extensive preexposure to the CS.…”
Section: Stimulus Processing Modelsmentioning
confidence: 50%
“…In taste-aversion learning in rats, rapid reacquisition has been observed (Revusky & Coombes, 1979), but "slow reacquisition" has been more common (Aguado, de Brugada, & Hall, 2001;Calton, Mitchell, & Schachtman, 1996;Hart, Bourne, & Schachtman, 1995). For example, Hart et al (1995) found that reacquisition was retarded relative to a "learningexperienced" control group that had received training and extinction with an orthogonal taste, for which there was little, if any, stimulus generalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further afield, there is recent evidence that rapid reacquisition can be considerably diminished in the rabbit NM preparation when there is massively extended extinction training-for example, 27 CS-alone trials for every original CS-US trial Medina, Garcia, & Mauk, 2001). These recent findings are heading in the direction of the retardation in reacquisition that has been seen in rats when extended extinction has been conducted (Bouton & Swartzentruber, 1986Carlton, Mitchell, & Schachtman, 1996;Hart, Bourne, & Schachtman, 1995; but see Aguado, de Brugada, Hall, & Agate, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, no control conditions were included to assess stimulus generalization decrement on the test. The novel combination of saccharin and vinegar may have distracted the E-group rats and/or disrupted their drinking (Aguado et al, 2001). This is of particular concern for Group 9E because it passed the test.…”
Section: Methodsmentioning
confidence: 99%